Формування диригентсько-хорової техніки майбутніх учителів музичного мистецтва у процесі створення художньої інтерпретації - Чжен Тунтун; Zheng Tungtung (Видавництво «Код», 2025)
Резюме. У статті розкривається проблема формування диригентсько-хорової техніки майбутніх учителів музичного мистецтва у процесі створення художньої інтерпретації. З’ясовано, що специфіка формування диригентсько-хорової техніки полягає в опосередкованому пізнанні музичного мистецтва, під час якого одночасно відбувається процес формування родових пізнавальних здібностей (ієрархічних класифікаторів вокальнохорової практики) і пошуки їх втілення засобами мануальних жестів (вказівних, експресивних, коригуючих та ін.).

Abstract. The article reveals the problem of formation of conducting and choral technique of future teachers of musical art in the process of creating artistic interpretation. It is found out that the specificity of formation of conducting and choral technique lies in indirect cognition of musical art, during which simultaneously the process of formation of generic cognitive abilities (hierarchical classifiers of vocal and choral practice) and search for their embodiment by means of manual gestures (indicative, expressive, corrective, etc.) occurs. It is determined that formation of students' ability to interpret choral works is carried out through in-depth analysis of musical styles, genres and eras, development of individual approach to performance, as well as through personal understanding of style, character, emotional content of the work. The ability to hear the entire work as a whole while working on a separate fragment and to imagine an interpretative version in one direction is valuable, avoiding unnecessary fluctuations in artistic decisions. It is revealed that an important factor in the formation of the conducting and choral technique of future teachers of musical art in the process of creating a musical interpretation is the ability to correctly determine the interpretative plan of a musical work. It is confirmed that the correct determination of the interpretative plan will reveal the artistic idea of the work, and also demonstrate the balance of various choral components in a single whole through the embodiment of the dramaturgy of the composer's idea and strengthening the emotional and personal experience of both the conductor and each singer-performer. It has been proven that artistic interpretation is a key factor in the development of conducting and choral technique of future teachers of musical art, as it forms the integrity of performing thought, activates creative thinking, and contributes to a deeper understanding of the style and content of musical material.
Formation of conducting and choral technique of future teachers of music in the process of creating artistic interpretation
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: хорове мистецтво; мануальний жест; художня інтерпретація; інтерпретаційний план музичного твору